A comparative study of kinematic and kinetic analysis of gait in patients with non-specific low back pain versus healthy controls - Mohammad Taghi Karimi; Maryam Hasan Zahraee; Mahmood Bahramizadeh; Hanieh Khaliliyan; Majid Ansari; Farhad Ghaffari; Arash Sharafatvaziri (Advances in Medicine, Psychology, and Public Health)
Introduction: Low back pain (LBP) is a common health and socioeconomic problem, especially the chronic one. It may affect the gait pattern of the patients. The aim of this study was to evaluate the motions of pelvis, trunk and legs in the subjects with non-specific chronic low back pain (NCLBP). Method: This was a cross-sectional study in which 40 subjects including 20 normal subjects and 20 NCLBP patients were recruited. The force applied on the leg, the range of motion of trunk, pelvic, lower extremity, the moments applied to the joints and spatiotemporal gait parameters were selected for this study. Results: The mean values of walking speed of normal subjects and NCLBP patients were 0.89 ± 0.13 and 0.95 ± 0.09 m/s, respectively (p=0.24). The mean value of the second peak of ground reaction force of normal and NCLBP subjects was 1.13 0.045 and 1.106 0.035 N/WB, respectively (p=0.038). Conclusion: There was a significant difference between the kinematics of the hip joints in the normal and NCLBP subjects. The interesting point of the current study was that those with NCLBP had a decrease in hip, knee, and ankle joint moments, maybe due to muscular weakness.